2005
DOI: 10.1016/j.ejcts.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic findings using tissue velocity imaging following passive containment surgery with the Acorn CorCap™ cardiac support device

Abstract: Addition of the Cardiac Support Device to conventional cardiac surgery improves patient status and decreases left ventricular size in heart failure patients with dilated cardiomyopathy. The positive effect on left ventricular dimensions is not accompanied by any improvement in cardiac output but rather right ventricular dysfunction, although the functional significance of this is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…A decrease in MR has not been observed in the trials to date 37 . A significant improvement in LVEF has not been demonstrated with CSD 32–35,37 . There have been no differences in all‐cause hospitalizations between CSD and non‐CSD groups 33 .…”
Section: Early Results Of Csdmentioning
confidence: 94%
“…A decrease in MR has not been observed in the trials to date 37 . A significant improvement in LVEF has not been demonstrated with CSD 32–35,37 . There have been no differences in all‐cause hospitalizations between CSD and non‐CSD groups 33 .…”
Section: Early Results Of Csdmentioning
confidence: 94%
“…However, tricuspid/mitral annulus motion recording by TVI has already been studied as a means of assessing human right/left ventricle function ( 18 ). Transmitral velocity depends on both preload and relaxation ( 3 ), whereas early diastolic mitral annulus velocity is dependent on left ventricle relaxation and independent of left ventricle fi lling pressure ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Slama et al ( 24 ) reported that E m was a reliable indicator in rats to evaluate ventricular relaxation and will be lower in rats with diastolic dysfunction. To evaluate systolic functions, we measured the tricuspid/ mitral annular peak systolic velocity instead of fraction shortening, ejection fraction, stroke volume, and cardiac output by conventional echocardiography ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACORN CorCap cardiovascular device (Acorn Cardiovascular, Inc., St. Paul, MN, USA) is one such device that has been tested in clinical trials as an isolated therapy or in conjunction with mitral valve surgery. Recent studies have shown both the safety and the benefit of passive restraint devices in patients with CHF, including decreased left ventricular dimensions and possibly improvement in left and right ventricular function [1][2][3]. These data are the basis for on-going clinical trials in Europe and North America.…”
Section: Introductionmentioning
confidence: 96%